Fields virology basic virology - Knipe, David M., (David Mahan), 1950- (Philadelphia : Lippincott-Raven Publishers, 1997)
Slides correspond to figures and tables in text : Fields virology, 3rd ed., 1996.
Keywords: Viruses -- slides; Virus Diseases -- slides